Notable family networks in latin america - Balmori, Diana; Voss, Stuart; Wortman, Miles (New York: The University of Chicago Press, 1984)
Contents : The family network,central america,northwest Mexico,Buenos Aires,the family network in the historical literature
Keywords: Family - Latin America